Potensi Aktivitas Farmakologi Senyawa Limonene pada Jeruk Kalamansi (Citrus microcarpa) - Haque, Aina Fakhil; Yogie Andika Tri Nanda; Dewi Winni Fauziah; Elly Mulyani (Gayaku Publisher, 2025)
Calamansi orange (Citrus microcarpa) is a type of small citrus fruit that comes from Southeast Asia and is widely cultivated in Indonesia. This fruit is known for its strong sour taste and distinctive fresh aroma. Its rich nutritional content, especially vitamin C, flavonoids and other phytochemical compounds, makes kalamansi orange have various health benefits. Several studies show that kalamansi oranges have high antioxidant activity so they are able to ward off free radicals and prevent cell damage. Apart from that, this fruit also has antimicrobial, anti-inflammatory properties, and can help increase the body's endurance. In the traditional health sector, kalamansi oranges are often used to relieve coughs, sore throats, and help digestion and detoxify the body because of their high citric acid content. In the food sector, kalamansi orange is used as a natural flavoring ingredient in drinks, sauces and processed foods because it can add a fresh taste. Meanwhile, in the cosmetics and skin care industry, calamansi orange extract is used because of its astringent properties which help reduce excess oil and brighten the skin. With extensive benefits and high economic value, kalamansi oranges have great potential for further development in various industrial sectors.